Total globozoospermia associated with increased frequency of immature spermatozoa with chromatin defects and aneuploidy: a case report - Vozdova, M; Rybar, R; Kloudova, S; Prinosilova, P; Texl, P; Rubes, J (Andrologia, 2014)
Globozoospermia, characterised by the presence of round spermatozoa lacking acrosomes in an ejaculate, is a known cause of male infertility. Semen analysis, including sperm chromatin structure assay, toluidine blue, chromomycin A3 and aniline blue staining and fluorescence in situ hybridisation, was performed in an infertile globozoospermic patient to establish to which extent these genetic factors contributed to his infertility. No spermatozoa capable of hyaluronan (HA) binding were detected in the HA binding assay. Increased rates of immature spermatozoa with defective replacement of histones by protamines, DNA breaks and disturbed chromatin integrity and sperm aneuploid for the sex chromosomes were observed. Intracytoplasmic sperm injection (ICSI) was used in three in vitro fertilisation (IVF) cycles, and enough morphologically well-developing embryos were obtained in each cycle. However, no pregnancy was achieved. The infertility of our couple, resistant to IVF/ICSI treatment, was most probably caused by a combination of male and female factors.
Keywords: dospělí; Female; aneuploidie; Adult; ženské pohlaví; lidé; Infertility, Male; Semen Analysis; Male; analýza spermatu; DNA Breaks; hybridizace in situ fluorescenční; lidé středního věku; mužská infertilita; mužské pohlaví; Aneuploidy; In Situ Hybridization, Fluorescence; Middle Aged; zlomy DNA; Humans